The Role of Cross-Cultural Communication in the Adaptation Process of Participants in the 2024 Mulawarman University Indonesian International Student Mobility Awards - Ananda Nazeli Ahsan; Johantan Alfando Wikandana Sucipta; Dony Kristian (Jurnal Indonesia Sosial Sains, 2026)
The increasing participation of students in international mobility programs has created new challenges related to cross-cultural adaptation, particularly in communication processes within unfamiliar cultural environments. The Indonesian International Student Mobility Awards (IISMA) program provides opportunities for students to gain global academic experiences; however, differences in language, cultural values, communication patterns, and social norms may influence their adaptation processes. This study aimed to analyze the role of cross-cultural communication in the adaptation process of 2024 IISMA participants from Mulawarman University based on Young Yun Kim’s Integrative Communication Theory. This research employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and literature reviews, while data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing/verification. The findings indicated that cross-cultural communication played a significant role in supporting students’ adaptation through six dimensions: host social communication, ethnic social communication, personal communication, environmental factors, predisposing factors, and cross-cultural transformation. Interactions with host communities and exposure to local media enhanced cultural understanding, while communication barriers and cultural differences initially generated stress during the adaptation process. Nevertheless, continuous interaction enabled students to develop communication competence, cultural awareness, and a cross-cultural identity. This study concluded that effective cross-cultural communication facilitated the transition from stress to adaptation and personal growth, enabling international students to successfully integrate into new cultural environments.